Relationship between Social Identification and Sport Participation amongst Staff of Developmental and Maintenance of Sports in Iran - Khabiri, Kaveh; Ghadimi, Bahram; Mehraein, Sepideh; Mehrad, Aida (Universitas Ahmad Dahlan, 2018)
Social identification determined as one of the imperative factor that specialized one society from the another one. In fact, this factor has been impacted by various items such as sport participation and appears comprehensively. Sport participation has considerable influence on health of society and conducts individualsâ identification in different ways. In this regard, the present study focused on the relationship between social identification and sport participation amongst 270 staff who are working on developmental and maintenance of sports in Iran. The data has been got based on Social Identification (Safarnia, 1993), and Participation Motivation Questionnaire (PMQ; Gill et al., 1983). The results showed that the sport participation has meaningful relation with social identification. In reality, the staff who considered on team working as participation and supply this main factor on their daily life shown better social identification.Â Keywords: Social Identification, Sport Participation, Staff, Iran